2017
DOI: 10.3390/en10111886
|View full text |Cite
|
Sign up to set email alerts
|

Charging Characteristics of Lithium Ion Battery Using Semi-Solar Modules of Polymer:Fullerene Solar Cells

Abstract: Abstract:The combination of lithium ion battery (LIB) and organic (polymer) solar cells is expected to deliver versatile self-rechargeable portable energy sources, but less attention has been paid to the charging characteristics of LIB-using polymer solar cells. Here we demonstrate that the LIB packs, which were prepared by using lithium cobalt oxide (LiCoO 2 ) and graphite as a cathode and an anode, respectively, can be effectively charged by semi-solar modules of polymer:fullerene solar cells, of which bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The significant increase in academic and professional research in this area points to many noteworthy possibilities (more on this can be found in research by, e.g. Akinyele et al, 2017, Song et al, 2017, Podder and Khan, 2016, and Gurung and Qiao, 2018, who wrote about the key advantages and disadvantages of batteries). What are the advantages of such a system?…”
Section: Prerequisites For a Solar Energy Modelmentioning
confidence: 99%
“…The significant increase in academic and professional research in this area points to many noteworthy possibilities (more on this can be found in research by, e.g. Akinyele et al, 2017, Song et al, 2017, Podder and Khan, 2016, and Gurung and Qiao, 2018, who wrote about the key advantages and disadvantages of batteries). What are the advantages of such a system?…”
Section: Prerequisites For a Solar Energy Modelmentioning
confidence: 99%